Pollen Visualization of Turkish Flora of Selected Plant Species under Light, Scanning, and Transmission Microscopy - Demirpolat, Azize; Sancar, Pelin Yilmaz (Mdpi, 2023)
This study aims to examine pollen morphologically via studies of 16 plant taxa from Turkish flora. The pollen structures of the taxa examined, and their microscopic relevance, was discussed and studied with the help of microscopic visualization using scanning and transmission microscopies. Pollen grains were first acetolyzed, and then quantitative and qualitative pollen features were used to evaluate the species. The pollen grains were prolate, spherical, elliptic, tricolporate, 3-colpate, and hexacolpate. Sculpturing patterns of surfaces vary from reticulate, micro-reticulate, and striate regulate. As the findings reveal, palynological data can aid in the taxonomic classification of Turkish floral species. Microscopic implications can be made via micromorphological examination to correctly identify the species. While the pollen morphology of 16 taxa collected from the study area was studied for the first time from this region, the palynological research of some taxa was introduced to the literature for the first time with this study. Pollen morphology and photographic and statistical data of the taxa in our study were determined. This study contributed to bee plant research, melisapalinological studies, and systematic botanical flora studies.
Keywords: Turkish flora; pollen morphology; surface; clustering analysis (CA); principle component analysis (PCA)